PHYSICAL AND PSYCHOLOGICAL SYMPTOMS OF MENOPOUSE IN WOMEN WITH A HISTORY OF HORMONAL CONTRACEPTIVE USE: A DESCRIPTIVE ANALYTICAL STUDY - Lailatul Fadliyah; Anestasia Pangestu Mei Tyas; Emuliana Sulpat; Amellia Mardhika; Anis Nur Laili; Yusfina Modesta Rua (Universitas Airlangga, 2026)
Introduction: Menopause is associated with a range of somatic and psychological symptoms that may be influenced by prior exposure to exogenous sex hormones. This study aimed to examine the association between a history of hormonal contraceptive use and the severity of physical and anxiety-related psychological symptoms among menopausal women. Methods: This cross-sectional analytical study enrolled 88 menopausal women aged 45–55 years from the Lamongan Community Health Center using purposive sampling. The Menopause Rating Scale (MRS) was used to assess somatic and urogenital symptom severity, while the Hamilton Anxiety Rating Scale (HARS) was used to quantify anxiety symptoms. Its use is reported here as a measure of anxiety rather than a broad index of all psychological complaints. Results: This study showed that 28.4% of menopausal women experienced severe physical complaints, 30.7% mild complaints, 26.1% no complaints, and the remaining 11.4% moderate complaints. Psychological complaints were mild in 27.3% of respondents, moderate in 11.4%, severe in 10.2%, and 39.8% reported no psychological complaints. The results of the statistical test, with a significance value of p = 0.029 (< 0.05), indicate that there is a relationship between a history of hormonal contraceptive use and psychological complaints in menopausal women. Conclusions: This study showed that 28.4% of menopausal women experienced severe physical complaints, 30.7% mild complaints, 26.1% no complaints, and the remaining 11.4% moderate complaints. Psychological complaints were mild in 27.3% of respondents, moderate in 11.4%, severe in 10.2%, and 39.8% reported no psychological complaints. The results of the statistical test, with a significance value of p = 0.029 (< 0.05), indicate that there is a relationship between a history of hormonal contraceptive use and psychological complaints in menopausal women.